Estudo da persistência e produção de leite de vacas da raça holandesa utilizando modelo de regressão aleatória - Dorneles, Cristian Kelen Pinto (2006)
A total of 21,702 test day milk yield records had been used of 2.429 first parity Holstein cows from 1991 and 2003, distributed in 33 herds of the state of Rio Grande do Sul, with the objective to estimate genetic parameters for persistence of lactation and milk production in the day of the control, to evaluate the relative efficiency of the selection for persistency in the lactation, and to estimate components of variance for test day milk yields. Three measurements had been analyzed of persistence in the lactation using the genetic values of the animals, gotten for the model of random regression adjusted by Legendre orthogonal polynomial of order 4. The residual variance was considered constant along the lactation. The estimates of herdability for the measures of persistence had varied from 0,0496 to 0,1977, the estimates of genetic correlations between the measures of persistence and the milk 305 day milk yields had varied from -0,0507 to 0,0717. The relative efficiency of the election for the measures of persistence presented better results for the third methodology of evaluation of the persistence. Among the measurements of persistency in the lactation evaluated in this study, we recommend the use of the P3 for the election of dairy cattle for bigger persistence in the lactation. The genetic variance of the milk production in the day of the control presented greaters values in the end of the lactation curve, increasing from the seventh control, presenting the greater estimative in the end of the lactation. The permanent variance of environment for milk production in the day of the control was bigger in the beginning and end of the lactation, initiating with 10,35, decreasing to 7,73, and finishing with 9,10, showing a bigger expression of the ambient factors in the beginning and end of the lactation. The estimates of herdability for milk production in the day of the control had been increasing gradual along the lactation curve, presenting the bigger estimate in the end of the curve. The genetic correlations had varied from 0,33 to 0,99. The genetic correlations had been bigger between close controls, as the proximity between the controls was bigger, greater the genetic correlation between them. The permanent environment correlations had followed the same trend that the genetic correlations, varying from 0,38 to 0,99. The smaller genetic correlations between the controls had been observed in the beginning and the end of the lactation curve. These facts suggest that the productions in the day of the control of the intermediate phase of the lactation curve can be used in the selection of dairy cattle.